2021
DOI: 10.3389/fpls.2021.772389
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bioactive Compounds of Sechium spp. for Therapeutic and Nutraceutical Supplements

Abstract: Natural products are in great demand because certain secondary metabolites (SMs) are sources of antioxidants, flavorings, active substances, or anticancer agents with less aggressiveness and selectivity, among which triterpenes and flavonoids are of importance because they inhibit carcinogenesis. For Sechium spp. P. Br. (chayotes), there is scientific evidence of antiproliferative activity that has occurred when cancer cell lines have been treated with this fruit. In order to compare future therapeutic designs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For this reason, some complementary therapeutic alternatives have been proposed such as the consumption of healthy foods, among which fruits and vegetables with a high content of antioxidants and an anti-inflammatory effect stand out [ 12 ]. In this regard, some studies have reported that S. edule has bioactive compounds with hypoglycemic, anti-inflammatory, antioxidant, hypotensive, and lipogenesis inhibitory effects [ 7 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, some complementary therapeutic alternatives have been proposed such as the consumption of healthy foods, among which fruits and vegetables with a high content of antioxidants and an anti-inflammatory effect stand out [ 12 ]. In this regard, some studies have reported that S. edule has bioactive compounds with hypoglycemic, anti-inflammatory, antioxidant, hypotensive, and lipogenesis inhibitory effects [ 7 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to have alternatives that help in the prevention of and reduction in symptoms of this syndrome. In this context, Sechium edule (chayote) ( S. edule ) is an edible plant of the Cucurbitaceae family, whose phytochemical analysis has shown the presence of cucurbitacins, polyphenols, and flavonoids that give it antioxidant, anti-inflammatory, hypoglycemic, hypotensive, as well as inhibitory effects of lipogenesis [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The constituents information of C. xanthorrhiza rhizome, S. edule fruit, and S. polyanthum leaf was obtained from the literature (Atanasov et al, 2021;Iñiguez-Luna et al, 2021;Ismail et al, 2019;Riviello-Flores et al, 2018) and Dr. Duke's Phytochemical and Ethnobotanical Databases. This database provides active compounds in every part of the plant thereby we can select active compounds from the appropriate part.…”
Section: Collection Of Active Compounds and Their Targets Predictionmentioning
confidence: 99%
“…Among some current uses of chayote are: its employment in the food industry due the production of starch; in the cosmetic industry, as an ingredient in moisturizers, cleansers, sun lotions, toothpastes, mouthwash, shaving creams, deodorants, and shampoos; and in the animal nutrition area due to its promotion of growth in pigs, because the chayote meals prepared with fruits and leaves were found to replace the standard grower ration in the diet of the pigs without any secondary effects; and this may be one of its most salient uses: in traditional medicine [ 129 ]. Chayote has been widely utilized in the treatment of diabetes, followed by uses such as a diuretic, in renal calculi, arteriosclerosis, hypertension, vermifuge, leprosy, and asthma [ 130 , 131 ].…”
Section: Selected Species Of the Cucurbitaceae Family Used In Mexico ...mentioning
confidence: 99%